Thoracolumbar partial lateral corpectomy for the treatment of chronic intervertebral disc disease in 107 dogs. Issue 1 (December 2015) - Ferrand, François-Xavier; Moissonnier, Pierre; Filleur, Aurélie; Cachon, Thibaut; Fau, Didier; Viguier, Eric; Carozzo, Claude
Abstract Background The purpose of this retrospective study was to assess short-and medium-term outcomes in dogs with chronic ventral thoracolumbar intervertebral disc disease (IVDD) treated by thoracolumbar partial lateral corpectomy (TLPLC). Dogs surgically treated for chronic ventral IVDD by TLPLC were included. For each dog, neurological status evolution and complications were reported. Factors that could have influenced neurological recovery were statistically tested. Results A total of 107 dogs were included in the study. Before surgery, 67.3 % of the dogs were able to walk, 24.3 % were grade 3, and 8.4 % were grade 4. The median hospitalization time was 3 days, and 82.2 % of the dogs were able to walk at discharge. The medium-term neurological grade was reached at a median time of 2 months. At the medium-term follow-up (median 12 months), 74.3 % of the dogs were neurologically improved, 22.9 % were stable, and 2.8 % were worsened. A total of 91.4 % of dogs were ambulatory, with 58.6 % of dogs having a normal gait. Preoperative neurological grade was significantly associated with the neurological status 24 h after the surgery and at discharge. Dogs with a higher preoperative neurological grade had a better chance of improving but lower odds of walking at 24 h after the surgery and at discharge compared with dogs with a lower preoperative grade. Spinal compression recurrence at the same surgical site was confirmed in 8 cases. Conclusion Even if TLPLC leads to several intra and postoperative complications, this technique is a viable surgical option to treat chronic ventral IVDD.